2015
DOI: 10.1061/(asce)he.1943-5584.0001218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Regionalization Methods for Hourly Continuous Streamflow Simulation Using Distributed Models in Boreal Catchments

Abstract: Regionalization for prediction in ungauged basins at hourly resolution is important for water resources management (e.g. floods and hydropeaking). In this paper, calibration of 26 catchments (39-3090 km 2 ) in mid-Norway was performed using hourly records and three spatially distributed (1x1 km 2 ) precipitation-runoff models: a first-order nonlinear system model (hereafter Kirchmod), the HBV model and the Basic-Grid-Model (BGM). Four regionalization methods for each model namely parameter set yielding maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…Wagener and Wheater, ) and uncertainty in identification of suitable regionalization methods (e.g. Hailegeorgis et al, ). The regression based prediction in the present study transfers characteristics of the observed streamflow from gauged to ungauged catchments while the regional calibration of the P–R model derives regional model parameters by utilizing the available streamflow data in the region.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Wagener and Wheater, ) and uncertainty in identification of suitable regionalization methods (e.g. Hailegeorgis et al, ). The regression based prediction in the present study transfers characteristics of the observed streamflow from gauged to ungauged catchments while the regional calibration of the P–R model derives regional model parameters by utilizing the available streamflow data in the region.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the algorithm is useful to calibrate large number of catchments at once. Hailegeorgis et al () obtained acceptable performance of the regional calibration based on transferring regional parameter set that provides maximum regional weighted average (MRWA) NSE compared to other advanced regionalization methods. In the present study, we also evaluated the performance of regional transfer of parameter sets that provide the best MRWA NSE compared to the regional regression model: 2.5emNSEMRWA=1NCtruetrue∑i=1NCa()niaNTSNSEi, where N Ca is the total number of catchments included to compute the NSE MRWA ( N Ca = N C − 1) since a donor catchment is excluded for the leave one out cross‐validation, n ia is the length of timestamp with non‐missing observed streamflow series for each catchment i and N TS is the total length of timestamp for the calibration period.…”
Section: Methods and Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other researchers also developed and evaluated methods that are potentially applicable for transferring infiltration parameterizations across scales. Hailegeorgis et al (2015) evaluated four regionalization methods for continuous streamflow simulation. Their regional calibration method uses the maximum weighted average of a performance measure such as the Nash-Sutcliffe efficiency to identify specific parameter sets per subpixel by the DREAM algorithm (Vrugt et al, 2009).…”
Section: Other Parameter Scaling Approachesmentioning
confidence: 99%